Leadership, Quality of Work Life and Self Development in Increasing Work Engagement for Polytechnic Lecturers LP3I Jakarta - Husein Tuasikal; Dedi Perwana; Usep Suhud (Journal Research of Social Science, Economics, and Management, 2022)
This research aims to analyze, interpret and evaluate Human Resources Management, especially at the LP3I Jakarta Polytechnic Management through a description of the influence of leadership, quality of work life and self-development on work engagement. This research uses regression analysis method and path analysis using a research sample of 110 people using accidental random sampling technique. The research sample in question is a lecturer in the Jakarta LP3I Polytechnic environment. The data collection technique used is the survey method through the distribution of online questionnaires. The results of this study show: (1) Leadership has a direct positive effect on ape attachment; (2) The quality of work life has a direct positive effect on work engagement; (3) Self-development has a direct positive effect on work engagement; (4) Leadership has a direct positive effect on self-development; (5) The quality of work life has a direct positive effect on self-development; (6) Leadership has a direct positive effect on the quality of work life; (7) Leadership has a positive indirect effect on work engagement through mediating self-development; (8) The quality of work life has a direct positive effect on work engagement through the mediation of self-development; (9) Leadership has a direct positive effect on self-development through mediating the quality of work life. Based on the results of the study, it was concluded that the level of work engagement of LP3I Jakarta Polytechnic Lecturers could be determined by the level of leadership, quality of work life and self-development. So this research provides advice to the Leaders & Management of the LP3I Polytechnic to improve leadership, especially at the head of the study program, improve the quality of lecturers' work life and provide a wider space for lecturers to develop themselves, so that Lecturers in the LP3I Jakarta Polytechnic environment have stronger work engagements. in order to carry out its duties to educate the nation's life and print human resources who are ready to enter the professional era.